PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PADA ATLET PUTRA BULUTANGKIS PB.ANGKASA PEKANBARU - Oktila, Siska Minami; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
techniques and quickly experience fatigue. The title examined in this study is "The Effect of Interval Training Training on Endurance in Badminton Male Athletes, PB." Angkasa Pekanbaru ". The purpose of this study to determine whether there is an increase in the endurance of badminton athletes. The form of this research is to use a one group pretest- postest design approach with a population of male badminton athletes PB.Angkasa Pekanbaru. The data in this study were the entire population, amounting to 8 people. The instrument used in this study is to use the Tesbalke test, which aims to determine how long the athlete's endurance has. To test for normality using the Lilifours test at a significant level of 0.05Î±. Based on the analysis of the normality test, the X data produces a LoMax of 0.250 and an Ltabel of 0.285, while the Y variable produces a LoMax of 0.254 and an L table of 0.285. This means that LoMax <Ltable, the data is normally distributed. Based on statistical data analysis, there is an average of 51.41 for the X variable and 51.61 for the Y variable. t table is (4.751)> (1,895), then Ha is accepted, in other words there is an effect of Interval Training on Endurance in Badminton Men's Athlete PB. Angkasa Pekanbaru.Key Words: Interval Training, Endurance